Comparison of Biocoenosis with Thanatocoenosis from Adriatic, between the peninsula Istria and the river Po - Šribar, Luka; Pavšič, Jernej (Geologija, 1993)
The comparison of biocoenosis and thanatocoenosis at three observational stations, west of the peninsula Istria, in littoral of the Adriatic sea, has shown a suprisingly low similarity between them. The difference seems to be due to ecological changes during the deposition of thanatocoenosis (approximately in the last hundert years). These ecological changes can not be studied in thanatocoenosis because of a very high degree of bioturbation that destroyed stratification and mixed all the skeletal particles. Lateral transport of skeletal particles seems to be of minor importance.